Health care providers' perceptions of barriers to perinatal mental healthcare in South Africa - Shelley Brown; Courtenay Sprague (BMC, 2021)
Abstract Background Perinatal mental disorders are a leading contributor to morbidity and mortality during pregnancy and postpartum, and are highly treatable when identified early. However, many women, especially in low and middle-income countries, lack access to routine identification and treatment of mental illness in public health settings. The prevalence of perinatal depression and anxiety disorders, common mental disorders, is three times higher for South African women relative to women in high-income countries. The public health system has begun to integrate mental health into maternal care, making South Africa a relevant case study of perinatal mental healthcare. Yet studies are few. We sought to investigate healthcare providers' perceptions of the barriers to early identification and screening of common perinatal mental disorders in public health facilities in South Africa. Methods Employing qualitative methods, we used purposive sampling to identify study participants, supplemented by snowball sampling. From September 2019-June 2020, we conducted in-depth interviews with 24 key informants in South Africa. All interviews were recorded and transcribed verbatim. We used a thematic approach to generate initial analytical themes and then conducted iterative coding to refine them. We adapted a delivery systems' framework to organise the findings, depicted in a conceptual map. Results Reported barriers to early identification and treatment of mental illness in the perinatal period encompassed four levels: (1) structural factors related to policies, systems and resources; (2) socio-cultural factors, including language and cultural barriers; (3) organisational factors, such as lack of provider preparation and training and overburdened clinics; and (4) individual patient and healthcare provider factors. Conclusion Barriers act across multiple levels to reduce quality mental health promotion and care, thereby creating an environment where inequitable access to identification of mental disorders and quality mental health services was embedded into systems and everyday practice. Integrated interventions across multiple levels are essential to improve the early identification and treatment of mental illness in perinatal women in South Africa. We provide recommendations derived from our findings to overcome barriers at each of the four identified levels.